2019
DOI: 10.1007/s42399-019-00149-3
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Multidrug-Resistant Bacteria in the Centre Hospitalier et Universitaire de la Mère et de l’Enfant Lagune (CHU-MEL) Reveals Implications of Poor Hygiene Practices in Healthcare

Abstract: Healthcare-associated infections represent an emerging public health issue with serious impact among hospitalized patients, including cesarized women and children with catheter. The present study determined the implications of hygiene practices and the hospital environment in wound reinfection among cesarized women and the occurrence of catheter-induced infections in children. Bacteriological analyses were performed on 100 wound swabs from cesarized women, 40 swabs from the wound dressing room, and 83 catheter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
2
9
2
Order By: Relevance
“…The comparison of the resistance profiles showed that there were the same profiles of circulating strains in the environment and wounds. The resistance proportions obtained for bacteria isolated from wounds and the environment in the present study are close to those of bacteria isolated from wounds and the environment at the University Hospital of Mother and Child-Lagoon (16). This study, therefore, confirms the role of the environment, especially the collection rooms, in the colonization of wounds in patients.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The comparison of the resistance profiles showed that there were the same profiles of circulating strains in the environment and wounds. The resistance proportions obtained for bacteria isolated from wounds and the environment in the present study are close to those of bacteria isolated from wounds and the environment at the University Hospital of Mother and Child-Lagoon (16). This study, therefore, confirms the role of the environment, especially the collection rooms, in the colonization of wounds in patients.…”
Section: Discussionsupporting
confidence: 85%
“…For Gram-negative bacilli, the performed tests were oxidase test, glucose fermentation test, and realization of the API 20E gallery for Enterobacteriaceae differentiation. Biochemical tests for the identification of Grampositive cohorts were catalase, free staphylocoagulase, and DNase production (16,18).…”
Section: Bacteriological Examinationmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Douard [26], it is therefore when the catheter is placed that the bacteria are inserted. A second factor linked to the occurrence of bacteremia is the quality of disinfection [27]. This includes hand hygiene, the quality of the antiseptic used for hand hygiene and disinfection of the operating site [28].…”
Section: Discussionmentioning
confidence: 99%